VietNam war films (McFarland, 1994)
The book discovers more than 600 VietNam War films. While the motion pictures dealing explicity with the VietNma War are seldom encoutered from the mid-1960s to 1977, several different genetic approaches nevertheless emerged during this period. They all treat the war in indirect and allegorical ways: biker movies (The born losers, Angles from hell, The losers, Chrome and hot leaders), westerns (The professional, The wild bunch, Soldier blue, Ulzana's raid), science fiction (Dark star), and even contemporary representations of World War II (The dirty dozen, Kelly's heroes). Each entry in filmography proper consists of several sections: a) Title (alternative titles), year, country, studio, color/BW, minutes. b) An asterick indicates the availability of the film on video (VHS). The asterick alone indicates availability in the U.S. (NTSC system); *SECAM means the film is available in the French VHS format (not yet in NTSC); *PAL means it is available in the British format (not yet NTSC). c) Major credits (director, producer, screenplay, editor, music, cast, etc.). d) A "Themes and key words" section presents a convenient checklist to the generic nature of the film. e) A synopsis. f) Comments that present the reviewer's analysis of the value of each film in artistic terms and its relevance to VietNam. Some films have either not survived or are not available for viewing. In these cases, the book has resorted to secondary source citations. Following the filmography, the Appendices include a chronology of films, film listing by country of origin (other than U.S.) lists of directors and their films and screen writers and their films, as well as a list of selected actors and their films. The final appendix provides a list of films that could not be examined but which might be fruitful subjects for further research